Asymptotic two-phase solitonlike solutions of the singularly perturbed Korteweg-de Vries equation with variable coefficients - Samoilenko, V. G.; Samoilenko, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We propose an algorithm of the construction of asymptotic two-phase soliton-type solutions of the Korteweg - de Vries equation with a small parameter at the higher derivative.